2009
DOI: 10.1364/josab.26.000a58
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and potential applications of ɛ-GaSe at terahertz frequencies

Abstract: Ordinary and extraordinary refractive indices of an ε-GaSe crystal at terahertz (THz) frequencies are experimentally determined in this study. Fitting experimental data by THz time-domain spectroscopy (THz-TDS) and a Fourier transform infrared spectrometer (FTIR), we proposed revised complex dielectric functions and Sellmeier equations of GaSe for both ordinary and extraordinary waves from 0.2 to 100 THz. Phonon vibrational modes and overtones in the THz frequency range are examined in detail. The high magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 29 publications
4
41
0
2
Order By: Relevance
“…With further study, the extraordinary refractive index for GaSe was found to be significantly lower, and the birefringence was found to be larger, than those values calculated using data from (Figure 11). 3,77,78 The dispersion equations for the ordinary refractive index referred to in papers 3,77,78 have a common origin in Palik's paper 79 ,which resulted in the similarity of the calculated curves (Figure 11a). …”
Section: Mid-ir Properties Of Al- Er- and Ag-doped Crystalsmentioning
confidence: 91%
See 2 more Smart Citations
“…With further study, the extraordinary refractive index for GaSe was found to be significantly lower, and the birefringence was found to be larger, than those values calculated using data from (Figure 11). 3,77,78 The dispersion equations for the ordinary refractive index referred to in papers 3,77,78 have a common origin in Palik's paper 79 ,which resulted in the similarity of the calculated curves (Figure 11a). …”
Section: Mid-ir Properties Of Al- Er- and Ag-doped Crystalsmentioning
confidence: 91%
“…In particular, a pair of Vodopyanov's dispersion equations 77 Doped GaSe for frequency conversion J Guo et al 6 dispersion equations for THz range have been proposed by Chen et al 3 The ordinary and extraordinary refractive indices for solid solutions GaSe 12x S x decrease in proportion to the mixing ratio magnitudes, from GaSe to GaS. Thus, the S-content in GaSe can be estimated from the refractive indices.…”
Section: Mid-ir Properties Of Al- Er- and Ag-doped Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…ε-polytype gallium selenide (hereinafter GaSe) promises efficient laser down-conversion almost over the entire THz range [2,3], except for the phonon absorption gap around 44 μm [2,4]. Owing to the large birefringence of GaSe (0.35 at 10 μm [5] and up to 0.79 [6] at 1 THz), phase matching can be achieved in multiple geometries: the common forward k 1 − k 2 = k 3 type II (oe → e) [2,3,[7][8][9][10][11]; (eo → e) [2] and (oe → o); [12], type I (ee → o) [10,13]; (oo → e) [14]; the original (ee → e) [15,16]; and backward type II (oe → e) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Gallium selenide (GaSe) is one of the most promising materials for conversion of optical frequencies in the infrared and terahertz spectral regions [1][2][3][4]. In comparison with other known noncentrosymmetrical chalcogenide crystals, GaSe possesses a high effective nonlinear coefficient and significant birefringence, which opens wide possibilities for phase matching between the interacting light waves [1, 4, and 5].…”
Section: Introductionmentioning
confidence: 99%